Growth performance, sexual reproduction and clonal propagation of Iris japonica Thunb. Natural populations in contrast reciprocal habitats on Jinyun Mountain, China - Qing, Yu Li; Jian, Ping Tao; Zhang, Cheng Zhong; Yong, Jian Wang (Universiti Kebangsaan Malaysia, 2014)
Growth performance, sexual reproduction and clonal propagation of I. japonica population in contrast reciprocal habitats; Open Area of Forest Edge (OAFE) and Bamboo Forest (BF) on Jinyun Mountain were studied to understand the adaptability of growth and reproductive of I. japonica in different habitats. The results were as follows: quantitative characteristics of growth and clonal propagation of I. japonica at genet (a group of genetically identical individuals, consists of whole ramets) level and at ramet (a unit composed of a shoot and root, with independent morphological and physiological traits in the same genet) level were higher in BF. However, quantitative characteristics of sexual reproduction at genet and ramet level were higher in OAFE. Biomass and allocation also showed the same trend as quantitative characteristics. Reproductive components (at ramet level) were significantly different and had trade-off in contrast reciprocal habitats. Allocation to clonal propagation and sexual reproduction of mother ramet was significantly negative correlation with allocation to daughter ramet (especially in BF). There was a trade-off between reproduction components (allocation to sexual reproduction and clonal propagation of mother ramet) in OAFE. Therefore, it showed predominantly sexual reproduction in OAFE and clonal propagation in BF. The results indicated that the contrast environmental stress shaping growth performance and reproduction variation of I. japonica in genet and ramet level in contrasting habitats might pronounce adaptive population differentiation among forest habitats.